Fat Grafting in Orthognathic Surgery. Issue 3 (May 2019) - Iyengar, Rajiv J.; Gabrick, Kyle; Bruckman, Karl; Steinbacher, Derek M.
Abstract : Background: Fat grafting is widely utilized in craniofacial surgery. The authors describe a series of consecutive patients who underwent orthognathic surgery with fat grafting by the senior author and review relevant literature in the field; fat grafting technique is discussed in detail. The authors also highlight 3 patients to illustrate postoperative outcomes. Methods: A retrospective cohort of consecutive orthognathic surgery patients was reviewed. Age, sex, BMI, procedure, area of harvest, location of injection, donor site complications, and need for repeat fat grafting were analyzed. Inclusion criteria included history of orthognathic surgery and concomitant fat grafting performed by the senior author in 2015. Results: Fifty-three orthognathic surgery patients with concurrent fat grafting were reviewed. The cohort comprised 20 males (37.7%) and 33 females (62.3%). Thirty-three patients (62.3%) underwent Le Fort I operations either in conjunction with genioplasty and/or bilateral sagittal split osteotomies. Twenty-eight patients (52.8%) underwent second operations involving additional fat grafting. The majority of these patients (15/28, 53.6%) received additional fat grafting during ensuing rhinoplasty. There were no donor site complications (ie, infection, wound breakdown) recorded in the authors' patient cohort. Amount of fat injected averaged 13.1 cc (range 5–25 cc). Follow-up generally occurred through the 1-year mark. Conclusions: Fat grafting is a proven technique to facilitate optimal postoperative wound-healing in orthognathic surgery. The senior author uses Telfa processing and the Coleman system to deliver the fat atraumatically. The authors' cohort of consecutive patients corroborates the benefits of fat grafting in craniofacial surgery; the authors observe wound-healing benefits, enhanced aesthetic outcomes and an anti-inflammatory effect with this technique.